“To brain or not to brain”: evaluating the possible direct effects of the satiety factor oleoylethanolamide in the central nervous system - Romano, Adele; Friuli, Marzia; Eramo, Barbara; Gallelli, Cristina Anna; Koczwara, Justyna Barbara; Azari, Elnaz Karimian; Paquot, Adrien; Arnold, Myrtha; Langhans, Wolfgang; Muccioli, Giulio G.; Lutz, Thomas Alexander; Gaetani, Silvana (Frontiers in Endocrinology, 2023)
Introduction Oleoylethanolamide (OEA), an endogenous N-acylethanolamine acting as a gut-to-brain signal to control food intake and metabolism, has been attracting attention as a target for novel therapies against obesity and eating disorders. Numerous observations suggested that the OEA effects might be peripherally mediated, although they involve central pathways including noradrenergic, histaminergic and oxytocinergic systems of the brainstem and the hypothalamus. Whether these pathways are activated directly by OEA or whether they are downstream of afferent nerves is still highly debated. Some early studies suggested vagal afferent fibers as the main route, but our previous observations have contradicted this idea and led us to consider the blood circulation as an alternative way for OEA’s central actions. Methods To test this hypothesis, we first investigated the impact of subdiaphragmatic vagal deafferentation (SDA) on the OEA-induced activation of selected brain nuclei. Then, we analyzed the pattern of OEA distribution in plasma and brain at different time points after intraperitoneal administration in addition to measuring food intake. Results Confirming and extending our previous findings that subdiaphragmatic vagal afferents are not necessary for the eating-inhibitory effect of exogenous OEA, our present results demonstrate that vagal sensory fibers are also not necessary for the neurochemical effects of OEA. Rather, within a few minutes after intraperitoneal administration, we found an increased concentration of intact OEA in different brain areas, associated with the inhibition of food intake. Conclusion Our results support that systemic OEA rapidly reaches the brain via the circulation and inhibits eating by acting directly on selected brain nuclei.